The effect of static stretching on maximal voluntary contraction and force-time curve characteristics - Papadopoulos, C.; Kalapotharakos, V. I.; Meliggas, K.; Gantiraga, E.; Prassas, S. (ISBS - Conference Proceedings Archive (Konstanz), 2006)
The purpose of this study was to examine the effect of static stretching of the lower limbs on maximal voluntary contraction (MVC) and isometric force-time curve characteristics (IFTC) of leg extensor muscles and integrated electromyographic activity of rectus femoris (EMGRF), biceps femoris (EMGBF) and gastrocnemius (EMGGS) muscles. Ten healthy physical education students were tested for MVC, IFTC, and EMG activity of the above muscles after a jogging and a jogging/stretch protocol of the lower limbs. There were no significant changes in MVC, IFTC, EMGBF, and EMGGS between jogging and jogging/stretch measurements. A significant decrease was observed in EMGRF. The results of this study indicated that a moderate volume of static stretching of the lower limbs did not impact significantly the majority of the variables examined.